Modulation of Pain Sensitivity by Chronic Consumption of Highly Palatable Food Followed by Abstinence: Emerging Role of Fatty Acid Amide Hydrolase - Cifani, Carlo; Avagliano, Carmen; Micioni Di Bonaventura, Emanuela; Giusepponi, Maria Elena; De Caro, Carmen; Cristiano, Claudia; La Rana, Giovanna; Botticelli, Luca; Romano, Adele; Calignano, Antonio; Gaetani, Silvana; Micioni Di Bonaventura, Maria Vittoria; et al. (Frontiers in Pharmacology, 2020)
There is a strong relationship between palatable diet and pain sensitivity, and the cannabinoid and opioid systems might play an important role in this correlation. The palatable diet used in many animal models of obesity is the cafeteria diet (CAF), based on human food with high sugar, salt, and fat content. In this study, we investigated whether long-term exposure to a CAF diet could modify pain sensitivity and explored the role of the cannabinergic system in this modification. Male Sprague-Dawley rats were divided into 2 groups: one fed with standard chow only (CO) and the other with extended access (EA) to a CAF diet. Hot plate and tail flick tests were used to evaluate pain sensitivity. At the end of a 40 day CAF exposure, EA rats showed a significant increase in the pain threshold compared to a CO rats, finding probably due to up regulation of CB1 and mu opioid receptors. Instead, during abstinence from palatable foods, EA animals showed a significant increase in pain sensibility, which was ameliorated by repeated treatment with a FAAH inhibitor, PF-3845 (10 mg/kg, intraperitoneally), every other day for 28 days . Ex vivo analysis of the brains of these rats clearly showed that this effect was mediated by mu opioid receptors, that was up regulated following repeated treatment of PF-3845. Our data add to the knowledge about changes in pain perception in obese subjects, revealing a key role of CB1 and mu opioid receptors and their possible pharmacological crosstalk, and reinforcing the need to consider this modulation in planning effective pain management for obese patients.